PERSEPSI KORUPSI PADA LAYANAN DIKLAT DI BALAI DIKLAT KEAGAMAAN BANDUNG TAHUN 2018 - Euis Setiawati (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
Corruptions in Indonesia are found in the public service sector. Bandung Education Training Center is a Training Center for the Ministry of Religion in the West Java Province which serves the public in the education and training sector. The purpose of this study was to describe the corruption perceptions by participants in training services at Bandung Education and Training Center. The research methodology used is descriptive quantitative analysis, using survey methods by processing data using the index formula. The research population was all training participants who have participated in training in Bandung Education and Training Center, the research sample was 545 respondents spread across 27 cities in West Java Province. The results of the study were that all training participants received the same education and training services, in all types of training that were followed, education technical training, religious technical training, and administrative technical training. The corruption perceptions of training participants in training services at Bandung Education and Training Center were on the corruption perception index of 4.32, meaning that the training services at Bandung Education and Training Center were in very good qualifications which did not indicate corruption Key Words: Perception; corruption; training services